The witching tree : a Natalie Lockhart novel - Blanchard, Alice (Blanchard, Alice. Natalie Lockhart series, 2021)
"In Alice Blanchard's The Witching Tree, Burning Lake is a small, isolated town with a dark history of witches and false accusations. Now, a modern-day witch has been murdered, and Detective Natalie Lockhart is reluctantly drawn deep into the case.."--